2016
DOI: 10.12669/pjms.323.10292
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood neutrophil lymphocyte ratio in the patients with postmenopausal osteoporosis

Abstract: Objective:To investigate the relationship between blood neutrophil lymphocyte ratio (NLR) and postmenopausal osteoporosis in Chinese women without diabetes.Methods:Two hundred and thirty three postmenopausal women without diabetes were included in this study. The clinical data of patients including age, and body mass index (BMI) were recorded. Blood samples were obtained to determine Blood urea nitrogen (BUN), Uric acid (UA), Albumin (ALB), Creatinine (CREA), Total Cholesterol(TC), Triglyceride (TG), Fasting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 13 publications
1
53
3
2
Order By: Relevance
“…Öztürk et al [19] found that NLR is an independent marker for osteoporosis and suggested that inflammation is present during bone remodeling [19]. Huang and Li [20] demonstrated a significant association between BMD and NLR in osteoporotic postmenopausal women [20]. In our study, there was no significant relationship between low BMD and NLR in patients with hemophilia.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Öztürk et al [19] found that NLR is an independent marker for osteoporosis and suggested that inflammation is present during bone remodeling [19]. Huang and Li [20] demonstrated a significant association between BMD and NLR in osteoporotic postmenopausal women [20]. In our study, there was no significant relationship between low BMD and NLR in patients with hemophilia.…”
Section: Discussioncontrasting
confidence: 43%
“…We found no significant differences in CBC, ESR, CRP, liver and renal functions, ALP, Alb, P, total bilirubin, and fasting blood glucose between the two groups. A few studies reported an association of NLR, PLR, and MPV with osteoporosis [19][20][21][22]. However, no previous study evaluated the association between low BMD and NLR, PLR and MPV in hemophiliacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some emerging studies suggested blood neutrophil‐to‐lymphocyte ratio (NLR). As a simple peripheral blood index which could reflect the systemic inflammatory level, NLR can well discriminate PMOP among postmenopausal women, even being superior to C reaction protein . However, to date, scarce study further explored if there are more optimal biomarkers other than NLR in blood routine examination for diagnosing PMOP, and if there are any blood biomarkers could predict fracture risk among PMOP patients.…”
Section: Introductionmentioning
confidence: 99%
“…The precise function of ALB and its role in OP are unclear. However, a previous study found that the expression of ALB differed significantly between a normal group and an OP group (P<0.05), and others have linked oxidative status with bone alterations (27)(28)(29). PHLPP2 is involved in the regulation of protein kinase B (Akt) and protein kinase C signaling, and mediates dephosphorylation in the C-terminal domain hydrophobic motif of members of the AGC serine/threonine protein kinase family.…”
Section: Discussionmentioning
confidence: 99%